Increasing the Listener of Pro 2 Radio Republik Indonesia (RRI) Semarang - Dwi Suci Citra Handa Lusia Ekta; M. Bayu Widagdo, S.Sos, M.I.Kom (Interaksi Online, 2017)
Radio Republic of Indonesia (RRI) is the only one radio which using the state names, its broadcast is pointed for the importance of state and nation. The function of RRI as a public broadcasting council and social control that independent, netral, and non commersial should give good information, education, good entertainment, and should keep national image in international world. Pro 2 is one of the program of RRI Semarang which exist on 95,3 FM waves Mhz. It had various broadcasting programs and it could be heard from 5 AM to 12 PM. Pro 2 RRI Semarang program has developed its broadcasting programs refers to life style, so that it make a special channel/program that pointed for youth. The purpose of this program as the umbrella organization to channel their inspiration and their talent in various fields and they could share and change their information suitable to their ages. The result of implementation the field works activity showed that through programs which chosen, we have increased the audiences of Pro 2 RRI Semarang program from 240 to 732 audiences on a month. The success of implementation of the field works activity in Pro 2 RRI Semarang program was resulted from the combination accurate of buzzing, interesting material, and with gift quizzes. The Project Manager and Public Relation responsible to cover all divisions and entire implementing activity in two ways communication and it also responsible to community relationship and stakeholder during doing field works activity.